An analytical study to determine prohibited anabolic residues in red meat tissue using LC-MS/MS system - NAZLI,Bülent (2022)
Abstract Hormones used for various purposes in animal breeding are not only important for animal health but also human health and thus meat and meat products need to be checked frequently for hormone residues. As the methods of detecting hormone residues in food samples are difficult and time-consuming, the present study was conducted with the aim of fast and practical determination of prohibited anabolic agents in red meat using LC MS-MS system. For this purpose, the QuEChERS method, which is widely used in pesticide and veterinary drug residue analysis was performed as below. Accordingly, (i) more polar solvent (Acetonitrile) was used in the sample preparation step and (ii) dispersive solid-phase solution was used instead of the solid phase extraction solution in the solution cleaning step. Furthermore, (iii) different groups were injected together in a single injection to analyze different types of anabolic substances with LC-MS/MS in the multi-component analysis phase. After the validation and determination of measurement uncertainty, 20 commercially available red meat tissues were analyzed, and the findings were compared to the literature. It was concluded that the applied method was found to be fast and reliable in the detection of prohibited anabolic agents in red meat tissue.